New Perspectives on the History of Facial Hair Framing the Face (Genders and Sexualities in History, 2018)
This volume brings together a range of scholars from diverse disciplinary backgrounds to re-examine the histories of facial hair and its place in discussions of gender, the military, travel and art, amongst others. Chapters in the first section of the collection explore the intricate history of beard wearing and shaving, including facial hair fashions in long historical perspective, and the depiction of beards in portraiture. Section Two explores the shifting meanings of the moustache, both as a manly symbol in the nineteenth century, and also as the focus of the material culture of personal grooming. The final section of the collection charts the often-complex relationship between men, women and facial hair. It explores how women used facial hair to appropriate masculine identity, and how women's own hair was read as a sign of excessive and illicit sexuality.